(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Looking at these pictures, one cannot believe that such places really exist on our planet. But this is the truth! Of course, we can’t help but admire that the skillful nature can create landscapes that amaze people. Today we bring to your attention the most amazing place on our planet. These hills, combined with the minarets of this mountainous salt mine, are considered a natural wonder. Until recently, these places were not given much attention, but the place is among the most amazing corners of the world, and the local government is determined to expand its infrastructure.